Lesser Armenia and its relations with the Bahri Mamluk state (595- 776 / 1198- 1375 AD) (Journal of the College of Basic Education, 2022)
The subject of the tagged research included Little Armenia and its relations with the Maritime Mamluk state (595-776 / 1198-1375 AD), which is the period extending from the establishment of the emerging state of Little Armenia in the southwestern part overlooking the Mediterranean, until its fall at the hands of the Mamluks. The first topic dealt with the geographical description and the establishment stage, and the second topic dealt with the establishment of the Kingdom of Little Armenia through the ceremony ceremonies and the official coronation of the king, while the third topic dealt with,